THE EFFECT OF THE LADDER DRILL-BASED METHOD ON THE ABILITY TO DRIBBLE FOOTBALL PLAYERS - Akhmad Sobarna; Sumbara Hambali; Kurnia Sandi; Supriadi, Idris; Henry Asmara (Cakrawala Pedagogik, 2023)
The purpose of this study was to determine the effect of the ladder drill-based method on the ability to dribble football players. The method used in this study was the experimental method, design "The One Group Pretest Posttest Design. 10-12 years who are enrolled in PS Pas FC and actively participate in training activities, namely as many as 30 people, the sampling technique used is saturated sampling technique, while the sample used is part of the population, amounting to 15 people. The data collection technique in this study used the dribbling test. Based on the results of the research analysis of the dribbling test, there is a difference, namely there is a significant difference in soccer players in the 10-12 year old group at PS Pas FC, with an average result of 24.2547 seconds. the final test (posttest) results increased by 23.4827 seconds. Data analysis used the t test at a significance level of 5%. The results showed that (1) there was a significant effect of ladder drill-based on the ability to dribble in the 10-12 year old group in PS Pas FC, with t count 7.987> 2.145 with a significance value of 0.001 <0.05.